AST-120 alleviates renal ischemia-reperfusion injury by inhibiting HK2-mediated glycolysis - Jinmeng Zhou; Jinbao Zhang; Feng Xu; Haijin Gao; Lei Wang; Yutong Zhao; Ke Li (BMC, 2024)
Abstract Objective Renal ischemia/reperfusion injury (IRI) is a major cause of acute kidney injury (AKI), which is associated with high incidence and mortality. AST-120 is an oral carbonaceous adsorbent that can alleviate kidney damage. This study aimed to explore the effects of AST-120 on renal IRI and the molecular mechanism. Methods A renal IRI mouse model was established and administrated AST-120, and differentially expressed genes were screened using RNA sequencing. Renal function and pathology were analyzed in mice. Hypoxia/reoxygenation (H/R) cell model was generated, and glycolysis was evaluated by detecting lactate levels and Seahorse analysis. Histone lactylation was analyzed by western blotting, and its relationship with hexokinase 2 (HK2) was assessed using chromatin immunoprecipitation. Results The results showed that HK2 expression was increased after IRI, and AST-120 decreased HK2 expression. Knockout of HK2 attenuated renal IRI and inhibits glycolysis. AST-120 inhibited renal IRI in the presence of HK2 rather than HK2 absence. In proximal tubular cells, knockdown of HK2 suppressed glycolysis and H3K18 lactylation caused by H/R. H3K18 lactylation was enriched in HK2 promoter and upregulated HK2 levels. Rescue experiments revealed that lactate reversed IRI that suppressed by HK2 knockdown. Conclusions In conclusion, AST-120 alleviates renal IRI via suppressing HK2-mediated glycolysis, which suppresses H3K18 lactylation and further reduces HK2 levels. This study proposes a novel mechanism by which AST-120 alleviates IRI.